Comparative analysis of serologic typing and HLA-II typing by micro-PCR-SSP - Wu, Da-Lin; Ling, Han-Xin; Ding, Hong; Zhang, Yi (Di 1 jun yi da xue xue bao = Academic journal of the first medical college of PLA, 2002)
To evaluate the accuracy of polymerase chain reaction with sequence specific primers (PCR-SSP) in HLA-II genotyping and analyze the causes of the errors occurring during the genotyping. Blood samples were obtained form patients with chronic renal insufficiency, leukemia or thalassemia and also from normal subjects. HLA-DR and -DQ genotyping of the sera from the 110 subjects was performed using micro-PCR-SSP and comparison was made with the results obtained from monoclonal antibody serologic typing. Of the 110 samples detected by micro-PCR-SSP, 396 alleles of HLA-DR were identified in 99 cases and 22 of HLA-DQ in 11 cases, and 10% of the subjects were identified as homozygote individuals. Examination by both of the 2 methods in 67 cases indicated high rates of missed diagnoses and misdiagnoses by serologic typing with the diagnostic discrepancy as high as 38.81% and 50.75% for HLA-DR and -DQ respectively. The antigens DR 15/16, 11/12, 13/14, 8 or 12; DQ 5/6, 8/9 were among those that frequently gave rise to errors or confusion. Micro-PCR-SSP method can accurately detect the alleles of HLA-II antigens that are easy to be missed or mistaken by serological typing method.